A Novel GLP-1R/fHCS Method to Determine the Bioactivity of Glucagon- Like Peptide 1(GLP-1) Analogous Drugs In Vitro - Wang, Jie; Lu, Ping; Zhang, Shengting; Li, Wanwan; Ji, Xiuling; Li, Jing; Zhang, Hui; Wei, Yunlin; Liang, Chenggang (Current Pharmaceutical Analysis, 2021)
Background: Current methods for assaying bioactivity of GLP-1 analogues are costly and time consuming, mainly dependent on AlphaScreen luminous beads, based on fluorescent resonance energy transfer technology, and cAMP-GloTM Max assay kit, and on ATP to generate a negative- association curve. Objective: To establish a sensitive, stable, and low-cost method for the determination of biological activity of therapeutic glucagon-like peptide-1(GLP-1) and their analogous drugs in vitro in quality control. Methods: An applicable fluorescent high-content system (fHCS) method was developed in U2OS cell, which was stably transfected with green fluorescent protein (GFP) labeled at the C-terminal of glucagon-like peptide-1 receptor (GLP-1R). HCS was firstly used to measure per unit area of fluorescent intensity changes as a result of drug-stimulated receptor endocytosis. Results: The detection sensitivity improved at least 30 folds than the other reported methods. This method showed a wide detection range with a good linear regression of R2>0.98. In five scgs from 50 150% SCG, the accuracy achieved the standard of the 41st United States Pharmacopoeia with all biases being less than 7.5%. The precision attained the 9.0th European Pharmacopoeia standard with all relative standard deviations (RSDs) below 10%. This assay result can be kept stable over 100 h at room temperature. Furthermore, the U2OS/GLP-1R cells showed a sharp specificity towards GLP-1 analogues during detecting activities in a mixture of different ligands. Conclusion: These results suggested that the GLP-1R/fHCS method can be employed broadly in the bioactivity determination of GLP-1 analogous drugs and as a platform for screening GLP-1 similar active ingredients in natural products.
Keywords: GFP labeled cell